Pengaruh Pemahaman Dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi pada KPP Pratama Jakarta Pesanggrahan Jakarta Selatan) - Fatimah, Fatimah; Nurhadi P, Elan (STIE AMKOP, 2024)
Introduction/Main Objectives: The importance of understanding taxation will raise awareness of taxpayers in carrying out their obligations, however, raising public awareness of taxpayers is not easy because public awareness is still low and there is a lack of information from the government. Background Problems: Lack of public attention regarding compliance with obligations in paying taxes. Efforts made such as outreach through print media and electronic media for WPOP are often ineffective due to various factors. Novelty: Taxpayer Understanding and Taxpayer Awareness have a positive and significant effect on Taxpayer Compliance. They realize that understanding and awareness of taxpayers has become an important part in increasing taxpayer compliance. Research Methods: The population was taken from individual taxpayers at KPP Pratama Jakarta Pesanggrahan as many as 137,024 people. The sample used in this research was 409 respondents and the data collection technique used a questionnaire with a LikeArt scale. To process the data, this research uses IBM SPSS Statistics 25 software with the analysis used, namely descriptive analysis, classical assumption test, multiple linear regression test, research instrument test, and hypothesis test. Findings/Results: Taxpayer understanding has a positive and significant effect with a value of 0.000